Exploring farmers’ willingness to pay for crop insurance products: A case of weather-based crop insurance in Punjab, India - K S Aditya,; Avinash Kishore,; Md Tajuddin Khan, (Agricultural Economics Research Review, 2023)
The Government of India has launched the Pradhan Mantri Fasal Bima Yojana, a crop insurance scheme that subsidizes the premium and promises to settle claims timely, but are farmers willing to pay? We conducted a contingent valuation study in Punjab, a state where agriculture is irrigated and the risk is estimated to be so low that the government has not implemented crop insurance before. The study is based on primary data of 716 wheat farmers. The study found that the farmers are willing to pay INR 297 per acre for crop insurance, less than the premium based on existing rates.